Project Based Learning (PBL) in Islamic Religious Education: Implementing Religious Moderation Values Through Student Collaborative Projects - Elvy Gustina; Zulfani Sesmiarni; Siska Margareta; Diana Sartika; Syafrudin Syafrudin (International Journal of Islamic Educational Research, 2025)
Islamic Religious Education (PAI) plays a crucial role in shaping students’ character and religious values, including moderate attitudes in practicing religion. This study aims to analyze the implementation of Project Based Learning (PBL) in PAI as a means to strengthen moderate character and integrate religious moderation values through student collaborative projects. The research employs a literature review approach, collecting data from various scientific literature, journals, books, theses, and dissertations relevant to the topic. Data analysis is conducted using content analysis and narrative synthesis, applying both deductive and inductive reasoning. The findings indicate that PBL allows students to actively engage in contextual real-life projects, making the understanding of Islamic teachings more applicable and reflective. PBL also promotes the internalization of religious moderation values through collaboration and discussion among students, while reinforcing moderate character by developing social skills, empathy, and inclusive attitudes. Despite challenges such as limited resources and teacher readiness, appropriate implementation strategies can optimize the effectiveness of PBL in PAI. Therefore, PBL functions not only as a learning method but also as a transformative pedagogical strategy that shapes a generation of Muslim students who are knowledgeable, tolerant, and moderate.